Slag and ardealite synergistic activated gypsum batten and preparation method thereof
By combining modified red mud ball milling with composite activators, along with self-healing microcapsules and stepped curing processes, the problems of unstable soluble phosphorus removal and insufficient slag activity activation in the co-application of slag and gypsum were solved, thus achieving high strength and improved durability of gypsum strips.
Patent Information
- Application Number
- CN202511070085.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-31
- Publication Date
- 2025-10-17
AI Technical Summary
The existing technology for the synergistic application of slag and gypsum has problems such as unstable removal of soluble phosphorus in phosphogypsum and limited activation effect of slag, resulting in limited room for improvement in the compressive strength of gypsum strips.
Pretreated phosphogypsum and modified red mud were ball-milled and combined with composite activators, reinforcing fibers and self-healing microcapsules to prepare slag phosphogypsum synergistic activated gypsum strips through a stepped curing process. This replaced the traditional acid washing method and single alkali activator, promoting the interfacial bonding and hydration reaction between slag and gypsum.
This process achieves a stable reduction in soluble phosphorus in phosphogypsum, fully activates the activity of slag, and improves the compressive strength, flexural strength, and durability of gypsum board panels. Moreover, the process is environmentally friendly and efficient.
Smart Images

Figure SMS_1
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of building materials, in particular to a kind of slag phosphogypsum cooperatively activated gypsum board and preparation method thereof. BACKGROUND
[0002] As a resource with high utilization value in industrial solid waste, slag is rich in silicate, aluminate and other active components, and has been applied in the field of gypsum board preparation. At present, the industry often mixes slag powder with gypsum base material, uses the potential hydration activity of slag to improve the mechanical properties and durability of gypsum board, realizes solid waste resource utilization, reduces material production cost, and meets the development trend of green building materials. Its application logic is mainly based on the reaction between slag and gypsum hydration products under certain conditions, which can supplement the gel phase, reduce the porosity of gypsum board, and thus improve the overall structural strength.
[0003] In view of the effect optimization of slag and gypsum cooperative application, the existing technology has carried out related improvement exploration. For example, by controlling the fineness of slag (such as increasing the specific surface area) to enhance its reaction activity, or using alkali activator (such as sodium hydroxide, water glass, etc.) to stimulate slag hydration, so as to improve its interface bonding capacity with gypsum base material; In the pretreatment of phosphogypsum, acid washing method is often used to remove harmful impurities such as soluble phosphorus, so as to avoid its adverse effect on gypsum setting time; In the curing process, steam curing and other methods are often used to accelerate the hydration reaction and shorten the curing period.
[0004] However, the existing technology still has obvious limitations: first, the removal of soluble phosphorus in phosphogypsum depends on acid washing method, which not only consumes a large amount of acid and increases cost, but also easily causes secondary pollution, and the phosphorus removal effect is not stable enough; Second, the activation of slag often depends on single alkali activator, which is difficult to fully activate the activity of slag, resulting in limited synergistic effect of slag and gypsum, and small space for improving the compressive strength of board. SUMMARY
[0005] In view of the technical defects in the background art, the present application proposes a kind of light high-strength waterproof gypsum board and its preparation method, which solves the above technical problems and meets the actual demand. The specific technical scheme is as follows: A kind of slag phosphogypsum cooperatively activated gypsum board, by weight, includes the following components: pretreated phosphogypsum 50-60 parts, slag powder 25-35 parts, composite activator 5-10 parts, reinforcing fiber 1-3 parts, self-repairing microcapsule 1-3 parts, foaming agent 0.1-0.5 parts, water 20-40 parts.
[0006] As a further technical scheme of the present application, the pretreated phosphogypsum is obtained by ball milling modification of phosphogypsum and modified red mud at a mass ratio of 9:1, the particle size D50 is ≤15 μm after ball milling, the soluble phosphorus content is ≤0.1%, the mineral powder is S95 grade blast furnace slag, and the specific surface area is ≥500 m 2 / kg.
[0007] As a further technical scheme of the present application, the composite activator is composed of nano-SiO2, CaO and metakaolin at a mass ratio of 3:4:3; the nano-SiO2 has a particle size of 20-50 nm, and the CaO has a purity of ≥95%.
[0008] As a further technical scheme of the present application, the reinforcing fiber is silanized basalt fiber, with a length of 3-6 mm and a diameter of 15-20 μm, and the self-repairing microcapsule is a microsphere with a lignin shell and a nano-silica sol core, with a particle size of 30-50 μm.
[0009] As a further technical scheme of the present application, the foaming agent is a compound of hydrogen peroxide and a protein-based foam stabilizer at a mass ratio of 1:1, and further includes a setting regulator of 0.3-0.8 parts, which is a compound of citric acid and borax at a ratio of 3:1.
[0010] A preparation method of a slag-phosphogypsum-activated gypsum strip board, comprising the following steps: S1. Preparation of pretreated phosphogypsum: mix phosphogypsum and modified red mud at a mass ratio of 9:1, ball mill to D50≤15 μm, then age at 60℃ for 24 h, centrifugal separation, and drying; S2. Preparation of self-repairing microcapsule: mix nano-silica sol and lignin solution at a volume ratio of 1:5, spray dry into microspheres, and solidify the shell by heat treatment at 150℃ for 1 h; S3. Preparation of slurry: dry mix pretreated phosphogypsum, mineral powder, and composite activator; add water and stir, then add reinforcing fiber, self-repairing microcapsule, and foaming agent in sequence, and stir uniformly to obtain slurry S4. Step-by-step curing: after the slurry is injected into a mold, pre-cure at 60℃ / RH≥90% for 4 h, then steam cure at 110℃ under normal pressure for 8 h, and then carbonization treatment with CO2 concentration of 20% for 24 h.
[0011] As a further technical scheme of the present application, in step S1, the ball milling uses zirconia milling beads, the ball-to-material ratio is 5:1, the rotation speed is 250 rpm, and the time is 2 h; in step S3, all components need to be dried at 105℃ to a water content of ≤0.5% before dry mixing; in step S4, the slurry is controlled to have a temperature rise rate of ≤5℃ / h during the pre-curing stage, and the CO2 pressure is 0.1 MPa during the carbonization treatment stage.
[0012] As a further technical scheme of the present application, the specific preparation method of the modified red mud is: Put the red mud raw material into the ball mill, add zirconia microspheres as grinding balls in a ball-to-material ratio of 6:1, add deionized water, and wet mill at a speed of 350 rpm for 1.5 hours to obtain a ball mill slurry, the diameter of the zirconia microspheres is 3-5 mm, the solid content of the ball mill slurry is 40-45%, 5% of the mass of the red mud sodium silicate solution is added to the ball mill slurry, and the ball mill slurry is transferred to a constant temperature stirring reaction kettle, stirred at 200 rpm at 80-85°C for 2h to obtain an activated slurry, the modulus of the sodium silicate solution is 1.8 and the concentration is 40%, the activated slurry is poured into a centrifuge, separated at a centrifugal force of 4000g for 10min, the supernatant is discarded, and the precipitate is washed repeatedly with deionized water three times until the conductivity of the filtrate is ≤100 μS / cm, the precipitate is dried in a 105°C air-drying oven until the water content is ≤2%, and then crushed through a 200 mesh sieve to obtain a red mud intermediate; Put the red mud intermediate into a muffle furnace, heat to 670±10°C at a rate of 5°C / min, keep for 45min, then take out the red mud intermediate and transfer it to a forced air cooling device, cool with 5°C cooling air, cool to below 80°C, and then cool to room temperature in a desiccator to obtain modified red mud.
[0013] As a further technical solution of the present application, the specific preparation method of the self-repairing microcapsule is: preparing a 20% lignin aqueous solution, adjusting the pH to 10.5-11.0, mixing the nanosilica sol with the lignin solution at a volume ratio of 1:5, high-speed dispersing at 1000 rpm for 30 min to form a homogeneous emulsion, and then performing spray drying by using a spray drying process, the spray drying conditions are: inlet temperature 180±5°C, outlet temperature 80±5°C, atomization pressure 0.3MPa, and the emulsion solid content is controlled to be 2%, and then the collected microspheres are heat treated at 150°C for 1h to make the lignin shell undergo glass transition to form a dense structure.
[0014] As a further technical solution of the present application, the specific method for preparing the pretreated phosphogypsum is: a) Put the phosphogypsum and the modified red mud into a ball mill in a mass ratio of 9:1, the ball mill uses zirconia ball milling beads, the ball-to-material ratio is 5:1, and wet milling is performed at a speed of 250 rpm for 2h to obtain a wet milling slurry; b) Transfer the wet milling slurry into an aging tank, and age at 60±2°C under stirring at a speed of 50 rpm for 24±0.5h; c) Separate the wet milling slurry after aging at a centrifugal force of 3500g for 5min, and discard the supernatant; d) Dry the precipitate in a 105°C hot air circulation oven until the water content is ≤0.5%, crush through a 325 mesh sieve, and obtain pretreated phosphogypsum with a D50 of ≤15μm.
[0015] The present application has the beneficial effects of: The application uses phosphogypsum, slag, modified red mud and other industrial solid wastes as main raw materials to realize resource utilization, the composite activator cooperatively activates the activity of the slag, the high specific surface area slag powder is used to enhance the interface bonding with the gypsum, the silicified basalt fiber improves the bending and tensile properties, the self-repairing microcapsule can repair microcracks to improve durability, and the foaming agent can reduce the self-weight, and through the step curing process, the gypsum board has high strength characteristics, in the process, the step curing process promotes the hydration and carbonation reaction, shortens the cycle and improves the strength and waterproofness, and the setting time regulator optimizes the setting time to ensure the construction performance. DETAILED DESCRIPTION
[0016] The embodiments of the application will be described below in conjunction with relevant examples, and the embodiments of the application are not limited to the following examples, and the application relates to related necessary components in the technical field, which should be regarded as known technology in the technical field and can be known and mastered by the person skilled in the art.
[0017] A slag-phosphogypsum-activated gypsum board comprises, by weight fraction, the following components: pretreated phosphogypsum 50-60 parts, slag powder 25-35 parts, composite activator 5-10 parts, reinforcing fiber 1-3 parts, self-repairing microcapsule 1-3 parts, foaming agent 0.1-0.5 parts, and water 20-40 parts.
[0018] In the pretreatment of the phosphogypsum, the application adopts the ball milling modification of the phosphogypsum and the modified red mud in a specific ratio to replace the traditional acid pickling and phosphorus removal process, which not only avoids the cost increase caused by the consumption of acid liquid in the acid pickling process, but also reduces the risk of secondary pollution from the root, and simultaneously, through the physical action of ball milling and the chemical synergy of the modified red mud, the content of soluble phosphorus in the phosphogypsum is stably reduced, the problem of unstable traditional phosphorus removal effect is solved, and the foundation for the performance stability of the subsequent gypsum board is laid.
[0019] The combination of the slag powder and the composite activator greatly improves the activity activation effect of the slag, the composite activator is composed of nano-SiO2, CaO and metakaolin, compared with a single alkali activator, it can promote the hydration reaction of the slag from multiple angles: nano-SiO2 participates in gel formation by virtue of high activity, CaO provides an alkaline environment to activate the potential activity of the slag, and metakaolin supplements the aluminum component to optimize the gel structure, through the above-mentioned synergistic activation effect, combined with the high specific surface area slag powder, the interface bonding capacity of the slag and the gypsum substrate is effectively enhanced, the gel phase is more sufficient, the porosity inside the board is effectively reduced, and the overall structural strength is improved.
[0020] The addition of reinforcing fibers and self-repairing microcapsules further optimizes the mechanical properties and durability of the strip board. The silanized basalt fibers, through surface modification, can better combine with the gypsum matrix and form a uniform support network inside the strip board, improving the bending strength and tensile properties of the strip board and reducing the risk of brittle fracture under stress. When microcracks appear in the strip board, the self-repairing microcapsules release the nano-silica sol core through shell rupture, filling and repairing the cracks, preventing further crack propagation, and thus prolonging the service life of the strip board.
[0021] As one of the preferred embodiments of the present application, the pretreated phosphogypsum is obtained by ball milling modified phosphogypsum and modified red mud at a mass ratio of 9:1, the particle size D50 is ≤15 μm, the soluble phosphorus content is ≤0.1%, the mineral powder is S95 grade blast furnace slag, and the specific surface area is ≥500 m 2 / kg.
[0022] The phosphogypsum and modified red mud are mixed at a ratio of 9:1, which can neutralize the soluble phosphorus in the phosphogypsum through the alkaline characteristics of the modified red mud, replacing the traditional acid washing method to avoid acid consumption and secondary pollution, and ensuring that the phosphogypsum as the main part of the substrate does not affect the basic properties of the gypsum matrix. Ball milling to a particle size D50 ≤15 μm can increase the specific surface area of the material, promote the full contact reaction of phosphogypsum and modified red mud, and reduce the soluble phosphorus to below 0.1%, solving the problem of unstable traditional phosphorus removal effect.
[0023] The mineral powder is S95 grade, which has high potential hydration activity; the specific surface area is set to ≥500 m 2 / kg, which further increases the contact area of the slag with the gypsum matrix and the composite activator, and can more fully respond to the activation effect, promote the hydration reaction and gel phase generation, and thus lay the foundation for synergistically enhancing the strength of the strip board with the phosphogypsum.
[0024] As one of the preferred embodiments of the present application, the composite activator is composed of nano-SiO2, CaO and metakaolin at a mass ratio of 3:4:3; the particle size of nano-SiO2 is 20-50 nm, and the purity of CaO is ≥95%.
[0025] Combining nano-SiO2, CaO and metakaolin at a mass ratio of 3:4:3 can form a multi-dimensional activation system: CaO with a purity of ≥95% can provide a sufficient alkaline environment to activate the hydration activity of silicates and aluminates in the slag, which is the basis for activating the slag; nano-SiO2 with a particle size of 20-50 nm has a large specific surface area and strong reactivity, and can directly participate in the hydration reaction, supplement the silicon elements needed for the gel phase, and reduce the defects of the hydration products; metakaolin provides an active aluminum source, which cooperates with silicon elements to form more stable aluminosilicate gel, solving the limitation of single alkali activator that can only promote part of the hydration reaction.
[0026] As one of the preferred embodiments of the present application, the reinforcing fiber is silanized basalt fiber, 3-6 mm in length and 15-20 μm in diameter, and the self-repairing microcapsule is a microsphere with a nanosilica sol core wrapped by a lignin shell, 30-50 μm in particle size.
[0027] The reinforcing fiber is selected as silanized basalt fiber, which is obtained by stirring and impregnating basalt fiber in 1% HK-570 / ethanol solution at a liquid-to-material ratio of 10:1 for 6 h and then drying at 100 ℃ for 24 h. The silanization treatment can improve the surface polarity of the fiber and make the interface between the fiber and the gypsum matrix more closely bonded. The silanized basalt fiber with a length of 3-6 mm and a diameter of 15-20 μm can ensure uniform dispersion of the fiber in the slurry and form effective "bridges" inside the strip board. When the strip board is stressed, the fiber can share the stress and prevent crack propagation, thereby improving the bending and tensile properties.
[0028] The self-repairing microcapsule adopts a nanosilica sol core wrapped by a lignin shell. The lignin shell has moderate brittleness and can accurately break when a microcrack is generated. The nanosilica sol core can flow to fill the crack and solidify to achieve self-repairing. The particle size of 30-50 μm matches the common microcrack size of the strip board, which will not break too early due to being too small, nor affect the compactness of the matrix due to being too large. The two work together to enhance the anti-cracking ability of the former and repair the generated cracks of the latter, thereby improving the mechanical stability and service life of the strip board.
[0029] As one of the preferred embodiments of the present application, the foaming agent is a mixture of hydrogen peroxide and a protein-based foam stabilizer at a mass ratio of 1:1, and further includes 0.3-0.8 parts of a setting regulator, which is a mixture of citric acid and borax at a ratio of 3:1.
[0030] The foaming agent is a mixture of hydrogen peroxide and a protein-based foam stabilizer at a ratio of 1:1. Hydrogen peroxide decomposes to produce oxygen to form bubbles when it comes into contact with water, and the protein-based foam stabilizer can form an elastic film on the surface of the bubbles to prevent the bubbles from merging or breaking. The ratio of 1:1 can balance the foaming efficiency and bubble stability, avoiding the problem of bubble collapse when foaming with single hydrogen peroxide, and ensuring the formation of uniform and small pores, which not only reduces the self-weight but also does not affect the structural integrity.
[0031] The setting regulator is a mixture of citric acid and borax at a ratio of 3:1. Citric acid delays the hydration of gypsum through adsorption, and borax adjusts the setting rate by forming a complex with gypsum ions. The ratio of 3:1 can control the setting time: it can avoid the problem of slow setting caused by excessive citric acid affecting production efficiency, and prevent the problem of fast setting caused by excessive borax hindering the pouring of the slurry.
[0032] A preparation method of a slag-phosphogypsum-activated gypsum strip board, comprising the following steps: S1. Pretreatment of phosphogypsum preparation: mix phosphogypsum with modified red mud at a mass ratio of 9:1, ball mill to D50≤15μm, then age at 60℃ for 24h, dry after centrifugal separation; S2. Self-repairing microcapsule preparation: mix nano-silica sol with lignin solution at a volume ratio of 1:5, spray dry into microspheres; heat treatment at 150℃ for 1h to solidify the shell; S3. Slurry preparation: dry mix pretreated phosphogypsum, slag powder, and composite activator; add water and stir, then add reinforcing fibers, self-repairing microcapsules, and foaming agent in sequence, stir uniformly to obtain slurry S4. Step curing: after the slurry is injected, pre-cure at 60℃ / RH≥90% for 4h, then steam curing at 110℃ for 8h, then carbonization treatment with CO2 concentration of 20% for 24h.
[0033] In the preparation method, the pretreatment of phosphogypsum is combined with ball milling, aging, and centrifugal separation of phosphogypsum and modified red mud, replacing traditional acid pickling to remove phosphorus, which not only avoids acid consumption and secondary pollution, but also stabilizes and reduces the soluble phosphorus content through ball milling to refine the particle size and aging reaction, while the modified red mud and phosphogypsum fully integrate to enhance the activity of the raw materials. The spray drying and heat treatment process of the self-repairing microcapsule can form a stable lignin shell, ensuring that the microcapsule does not rupture prematurely during slurry stirring and molding, and only releases nano-silica sol when a crack occurs, ensuring repair effectiveness. The dry mixing and stepwise feeding during slurry preparation avoid water interference and ensure uniform dispersion of each component, enhancing the synergistic effect between materials.
[0034] The step curing process is the most breakthrough: pre-curing avoids cracks caused by sudden temperature changes; main curing accelerates the hydration reaction to promote gel formation; carbonization treatment allows Ca(OH)2 to react with CO2 to form calcium carbonate, filling pores to improve density and water resistance. The entire curing process shortens the cycle while simultaneously improving strip strength and durability. The addition of a setting retarder coordinates the process rhythm, ensuring the workability of the slurry, ultimately enabling the production of lightweight, high-strength, durable, and waterproof gypsum strips in an environmentally friendly and efficient manner.
[0035] As one of the preferred embodiments of the present application, the ball milling in step S1 uses zirconia ball milling beads, the ball-to-material ratio is 5:1, the rotation speed is 250rpm, and the time is 2h. Before dry mixing in step S3, all components need to be dried at 105℃ to a water content of ≤0.5%.
[0036] Further, the specific method for preparing the pretreated phosphogypsum is: a) Add phosphogypsum and modified red mud to a ball mill at a mass ratio of 9:1, the ball mill uses zirconia ball milling beads, the ball-to-material ratio is 5:1, and the wet milling is carried out at a rotation speed of 250rpm for 2h to obtain wet-milled slurry; b) The wet grinding slurry is transferred to the aging tank and aged at 60±2℃ with a stirring speed of 50rpm for 24±0.5h; c) The wet grinding slurry after aging is separated by centrifugation at 3500g for 5min, and the supernatant is discarded; d) The precipitate is dried in a hot air circulating oven at 105℃ to a moisture content of ≤0.5%, crushed through a 325 mesh sieve, and a pretreated phosphogypsum with a D50≤15μm is obtained.
[0037] In the preparation step of the above pretreated phosphogypsum, a ball-to-material ratio of 5:1, a rotation speed of 250rpm, and a duration of 2h can not only refine the material to a D50≤15μm through sufficient grinding intensity, but also avoid excessive grinding that leads to energy waste. Meanwhile, the wet grinding environment can promote the uniform mixing of phosphogypsum and modified red mud, creating conditions for subsequent reactions.
[0038] The temperature of 60±2℃ in the aging stage can accelerate the reaction between the alkaline components of the modified red mud and soluble phosphorus, and the stirring at 50rpm ensures uniform contact of the slurry for reaction. The duration of 24±0.5h ensures that the reaction proceeds sufficiently, causing the soluble phosphorus to stabilize at the target value. The combination of 3500g centrifugal force and 5min can efficiently separate the supernatant of soluble impurities generated by the reaction, improving the impurity removal efficiency. Drying at 105℃ to a moisture content of ≤0.5% can eliminate the interference of water on the subsequent slurry ratio, and the 325 mesh sieve further controls the uniformity of particle size.
[0039] As one of the preferred embodiments of the present application, the slurry temperature rising rate in the pre-curing stage of step S4 is controlled to be ≤5℃ / h, and the CO2 pressure in the carbonation treatment stage is 0.1MPa.
[0040] Controlling the temperature rising rate to ≤5℃ / h in the pre-curing stage can avoid thermal stress caused by internal and external temperature differences due to sudden temperature rise of the slurry. The gypsum structure is loose in the early stage of hydration, and if the temperature rises too fast, internal moisture migration and volume change are easy to cause micro-cracks, while slow temperature rise can make the hydration reaction proceed uniformly, allowing the gel phase to gradually form a stable skeleton, laying a foundation for subsequent strength improvement.
[0041] The combination of CO2 pressure of 0.1MPa and humidity of 70% in the carbonation treatment stage precisely controls the carbonation reaction efficiency. The pressure of 0.1MPa can promote CO2 to penetrate into the internal pores of the strip and react with the Ca(OH)2 generated by hydration to form calcium carbonate; the humidity of 70% can maintain the humid environment required for the reaction, avoiding interruption of the reaction due to excessive drying, while preventing too high humidity from hindering the diffusion of CO2. The combination of the two makes the carbonation reaction more complete, and the generated calcium carbonate fills the pores, not only improving the density and compressive strength of the strip, but also enhancing the waterproof performance.
[0042] As one of the preferred embodiments of the present application, the specific preparation method of the modified red mud is as follows: Put the red mud raw material in the ball mill, add zirconium oxide microspheres as grinding balls according to a ball-to-material ratio of 6:1, add deionized water, wet mill at a speed of 350 rpm for 1.5 hours to obtain a ball-milled slurry, the diameter of the zirconium oxide microspheres is 3-5 mm, the solid content of the ball-milled slurry is 40-45%, add a sodium silicate solution with a mass fraction of 5% of the red mud to the ball-milled slurry, transfer to a constant-temperature stirring reaction kettle, stir at 200 rpm at 80-85°C for 2 hours to obtain an activated slurry, the modulus of the sodium silicate solution is 1.8 and the concentration is 40%, pour the activated slurry into a centrifuge, separate at a centrifugal force of 4000g for 10 minutes, discard the supernatant, wash repeatedly with deionized water three times until the conductivity of the filtrate is ≤100 μS / cm, dry the precipitate in a 105°C air-drying oven until the water content is ≤2%, crush to pass through a 200-mesh sieve to obtain a red mud intermediate; Put the red mud intermediate in a muffle furnace, heat to 670±10°C at a rate of 5°C / min, keep the temperature for 45 min, then take out the red mud intermediate and transfer to a forced air cooling device, cool with 5°C cooling air until the temperature is below 80°C, then place in a desiccator to cool to room temperature to obtain modified red mud.
[0043] In the specific preparation method of the modified red mud, the red mud raw material is refined by ball milling and activated by sodium silicate to form an active structure with a high specific surface area, which is rich in free alkali and active silica-aluminum components. When pretreating phosphogypsum, it can efficiently react with soluble phosphorus to form stable phosphate, replacing traditional acid washing to remove phosphorus, which not only avoids acid pollution, but also stabilizes soluble phosphorus to below 0.1%, ensuring normal coagulation of gypsum. At the same time, the alkaline nature of the modified red mud provides an initial alkaline environment for slag hydration, and cooperates with the composite activator to activate the slag activity: the released silicon-aluminum ions complement the nano-SiO2 and metakaolin in the slag and composite activator, promoting the formation of aluminosilicate gel, strengthening the interface bonding between the gypsum matrix and the slag, reducing the porosity, and improving the compressive strength of the board.
[0044] Add a sodium silicate solution with a mass fraction of 5% of the red mud and react at 80-85°C for 2 hours. During this process, the active silicon-oxygen groups contained in the sodium silicate as an activator will react with metal oxides such as aluminum and iron in the red mud to form silico-aluminate intermediates with high reactivity. At the same time, the alkaline nature of sodium silicate can adjust the pH value of the red mud and enhance its overall alkalinity. The 4000g centrifugal force separation and multiple washing until the conductivity is ≤100 μS / cm are to remove the originally contained soluble salts (such as sodium and potassium salts) in the red mud to avoid these impurities migrating to the surface of the board when mixed with phosphogypsum in the subsequent process, causing frosting or affecting the coagulation and hardening of the gypsum.
[0045] The calcination and cooling process further enhances the activity of the red mud. The amorphous mineral phase in the red mud is restructured by calcination to generate more metastable structures with potential hydration activity, which can also avoid excessive growth of crystals at high temperatures to reduce activity. Insufficientness of the structure transformation is ensured by heat preservation for 45 min, and then rapid air cooling to below 80℃, which inhibits the growth of crystals through quenching and retains a large number of high-activity fine grains, so that the red mud can release activity more quickly in the subsequent reaction with phosphogypsum and slag.
[0046] As one of the preferred embodiments of the present application, the specific preparation method of the self-repairing microcapsule is as follows: a 20% lignin aqueous solution is prepared, the pH is adjusted to 10.5-11.0, a nanosilica sol is mixed with the lignin solution at a volume ratio of 1:5, high-speed dispersion is carried out at 1000 rpm for 30 min to form a homogeneous emulsion, spray drying is carried out by using a spray drying process, the spray drying conditions are as follows: inlet temperature 180±5℃, outlet temperature 80±5℃, atomization pressure 0.3 MPa, and the emulsion solid content is controlled to be 2%, and then the collected microspheres are heat treated at 150℃ for 1 h to make the lignin shell undergo glass transition to form a dense structure.
[0047] In the above preparation method, the nanosilica sol and the lignin solution are mixed at a volume ratio of 1:5, which not only ensures sufficient content of the core repair material, but also forms a complete shell through excess lignin; high-speed dispersion at 1000 rpm for 30 min can break the agglomeration and form a homogeneous emulsion, The parameters of spray drying accurately control the morphology of the microspheres: the inlet temperature is 180±5℃ to quickly evaporate the water in the droplets, and the outlet temperature is 80±5℃ to avoid inactivation of the nanosilica sol due to high temperature; the atomization pressure is 0.3 MPa to form droplets with uniform particle size, and the solid content is controlled to be 2% to control the particle size of the microspheres to be 30-50 μm. Heat treatment at 150℃ for 1 h promotes the glass transition of the lignin shell to form a dense structure.
[0048] It should be noted that the nanosilica sol core is wrapped in the lignin solution to form a "sol-in-water" emulsion structure. In the initial stage of spray drying (high temperature section of the inlet), the water on the surface of the droplets evaporates quickly to form a solid lignin shell, and the internal silica sol is always ≤80℃ due to incomplete evaporation of water, and at the same time, the high temperature (180℃) of the inlet only acts on the surface layer of the atomized droplets, and the internal droplets form a self-cooling effect due to water evaporation and heat absorption, so that the temperature of the core is maintained below 60℃.
[0049] Example 1 A method for preparing a gypsum strip board by synergistically activating slag and phosphogypsum, comprising the following steps: S1. Preparation of pretreated phosphogypsum The phosphogypsum and the modified red mud were added into a ball mill at a mass ratio of 9:1, zirconia ball milling beads were used (ball-to-material ratio of 5:1), and wet milling was performed at a speed of 250 rpm for 2 h; the wet-milled slurry was transferred into an aging tank, and was aged at 60 ± 2 ℃ under stirring at a speed of 50 rpm for 24 ± 0.5 h; after aging, the slurry was separated by centrifugation at a centrifugal force of 3500 g for 5 min, and the supernatant was discarded; the precipitate was dried in a hot air circulation oven at 105 ℃ to a water content of ≤0.5%, was crushed through a 325 mesh sieve, and pretreated phosphogypsum with a D50 of ≤15 μm was obtained.
[0050] S2. Preparation of self-repairing microcapsules A 20% lignin aqueous solution was prepared, and the pH was adjusted to 10.5-11.0; the nano-silica sol was mixed with the lignin solution at a volume ratio of 1:5, and was dispersed at a high speed of 1000 rpm for 30 min to form a homogeneous emulsion; spray drying was performed by using a spray drying process (inlet temperature of 180 ± 5 ℃, outlet temperature of 80 ± 5 ℃, atomization pressure of 0.3 MPa, and solid content of the emulsion of 2%), and the collected microspheres were heat-treated at 150 ℃ for 1 h to cause glass transition of the lignin shell and form a dense structure.
[0051] S3. Preparation of slurry The pretreated phosphogypsum 55 parts, S95 grade slag powder (specific surface area ≥ 500 m 2 / kg) 30 parts, and composite activator (nano-SiO2:CaO:metakaolin = 3:4:3) 7 parts were dry mixed; 30 parts of water was added and stirred, and then basalt fiber silanized (length 6 mm, diameter 20 μm) 2 parts, self-repairing microcapsules 2 parts, and compound foaming agent (hydrogen peroxide: protein foam stabilizer = 1:1) 0.3 parts were added in sequence, and stirring was performed until uniformity was achieved, to obtain the slurry.
[0052] S4. Step curing After the slurry was injected into a mold, pre-curing was performed at 60 ℃ / RH ≥ 90% for 4 h (temperature rising rate ≤ 5 ℃ / h), then main curing was performed at 110 ℃ under normal pressure steam for 8 h, and finally carbonization treatment was performed at a CO2 concentration of 20%, a pressure of 0.1 MPa, and a humidity of 70% for 24 h.
[0053] Comparative Example 1 The difference from Example 1 is that the modified red mud pretreatment was cancelled, and a traditional acid washing method was used to treat the phosphogypsum (washing with 5% dilute sulfuric acid for 3 times → washing with water until neutral → drying and crushing); the ball milling and aging step of step S1 was cancelled, and the acid-washed phosphogypsum was directly used; curing was performed by using 110 ℃ steam curing for 12 h (step curing was cancelled). The remaining components and preparation process were unchanged.
[0054] Comparative Example 2 The difference from Example 1 is that the composite activator was replaced by a single alkali activator, water glass (modulus 1.2, solid content 40%) 7 parts. The remaining components and preparation process were unchanged.
[0055] Comparative Example 3 The difference from Example 1 is that the lignin shell / nano-silica sol core microcapsules are replaced by melamine resin shell wrapped epoxy resin core microcapsules (particle size 30-50 μm) 2 parts. The rest of the components and preparation process remain unchanged.
[0056] Comparative Example 4 The difference from Example 1 is that the step curing is cancelled and a single curing mode is used (direct 110°C normal pressure steam curing for 12h after molding, cancelling pre-curing and carbonization treatment). The rest of the components and preparation process remain unchanged.
[0057] Comparative Example 5 The difference from Example 1 is that (1) the modified red mud modification is cancelled (use raw phosphogypsum); (2) the composite activator is cancelled; (3) the self-repairing microcapsule is cancelled. The component adjustment is: raw phosphogypsum 55 parts, S95 slag powder 30 parts, silanized basalt fiber 2 parts, compound foaming agent 0.3 parts, water 30 parts. The preparation process is adjusted to: direct mixing and molding → 60°C curing for 24h.
[0058] Comparative Example 6 The difference from Example 1 is that an equal amount of unmodified red mud is used instead of modified red mud to replace the pre-treatment phosphogypsum preparation in step S1, and the rest of the components and preparation process remain unchanged.
[0059] Comparative Example 7 The difference from Example 1 is that ball milling is cancelled in step S1, and phosphogypsum and modified red mud are only dry mixed, and the rest of the components and preparation process remain unchanged.
[0060] Comparative Example 8 The difference from Example 1 is that the compound activator is adjusted to: nano-SiO2: CaO: metakaolin = 1:4:5, and the rest of the components and preparation process remain unchanged.
[0061] Performance Evaluation According to JGT169-2016, the compressive strength MPa, bending failure load, and impact resistance of Example 1 and Comparative Examples 1-8 (90mm plate thickness) were tested, and the test results are shown in the following table:
[0062] From the performance data comparison of Example 1 and each comparative example, the specific effects of each technical means on the performance of the gypsum board can be determined, and the main conclusions are as follows: The compressive strength of Comparative Example 1 is about 25% lower than that of Example 1, and the bending failure load and impact resistance are also significantly reduced. This shows that the modified red mud can not only remove soluble phosphorus through physical and chemical synergistic stabilization, but also can improve the activity of phosphogypsum through ball milling and aging reaction; and the step curing (pre-curing to avoid cracks, main curing to accelerate hydration, and carbonation to fill pores) effectively improves the density and structural stability of the strip through staged reaction, which is better than single steam curing.
[0063] After replacing the composite activator with single water glass in Comparative Example 2, the compressive strength is reduced to 4.8 MPa, which is about 30% lower than that of Example 1. This confirms the synergistic effect of nano-SiO2, CaO, and metakaolin. CaO provides an alkaline environment, nano-SiO2 supplements active silicon, and metakaolin introduces active aluminum, all of which together promote the hydration of slag to generate more stable gel phase. Single alkali activator cannot achieve multi-dimensional activity activation, resulting in a significant weakening of the synergistic effect of slag and gypsum.
[0064] After replacing the microcapsule type in Comparative Example 3, the impact resistance is reduced from 9 times to 5 times, with a decrease of nearly 45%, while the compressive strength only decreases slightly. This is because the lignin shell can accurately break when micro-cracks occur, and the released nano-silica sol can quickly fill the cracks and solidify, effectively preventing crack propagation. The microcapsules used for comparison (melamine resin shell + epoxy resin core) have lower repair efficiency and are difficult to deal with micro-damage caused by impact, so the impact resistance is reduced.
[0065] After canceling pre-curing and carbonation treatment and only using single steam curing in Comparative Example 4, the compressive strength is about 28% lower than that of Example 1. This shows that the slow heating of pre-curing can avoid the initial cracks caused by thermal stress in the slurry, and the carbonation treatment generates calcium carbonate by reacting CO2 with hydration products, further filling pores and improving structural density. The "step" strengthening formed by the combination of the two with the main curing is a key process guarantee for the strength and durability of the strip.
[0066] After canceling the modified red mud modification, composite activator, and self-repairing microcapsule in Comparative Example 5, the compressive strength is only 3.5 MPa, and the bending and impact resistance are also the worst. This shows that the modified red mud pretreatment solves the activity and impurity problems of phosphogypsum, the composite activator activates the slag and enhances the performance, and the self-repairing microcapsule improves the damage repair ability. The three together with the step curing process form a complete system for performance improvement. The absence or replacement of a single technology will result in a significant decrease in performance. Only the synergistic effect can achieve the effect of "lightweight, high-strength, and durable impact resistance" of the strip.
[0067] The compressive strength, bending failure load and impact resistance of Comparative Example 6 are all significantly lower than those of Example 1, because the unmodified red mud is replaced with an equal amount of modified red mud. The modified red mud plays a decisive role in improving the overall performance of the gypsum board. The unmodified red mud contains a large amount of inert crystalline phases (such as hematite and quartz) and soluble salts (Na+ and K+), which can only provide physical filling effect. Although the compressive strength (4.2 MPa) of the unmodified red mud is slightly higher than that of the system without red mud (3.5 MPa of Comparative Example 5), it is significantly lower than that of the modified red mud system (6.9 MPa). At the same time, the soluble salts remaining in the unmodified red mud migrate to the interface of the matrix, causing efflorescence, weakening the bonding force between the fibers and the gypsum, resulting in a decrease in the bending load (2.7 times the weight) compared to Example 1 (4.0 times). In addition, the incomplete neutralization of soluble phosphorus further inhibits the hydration reaction, resulting in an impact resistance (4.5 times) less than half of that of Example 1 (9 times). This fully proves that the modification process (ball milling for salt removal-sodium silicate activation-calcination for crystalline phase reconstruction) converts red mud from an inert filler to a high-activity functional material, which releases active silicon and aluminum components to synergistically stimulate slag, stabilize and solidify soluble phosphorus, and optimize the pore structure, which is the core innovation point of achieving lightweight and high-strength (compressive strength > 6.5 MPa) and durable impact resistance of the board.
[0068] In Comparative Example 7, the ball milling process in Step S1 is cancelled, and only phosphogypsum and modified red mud are dry mixed. The performance of the gypsum board is slightly lower than that of Example 1. Ball milling can finely grind the materials to D50≤15μm through mechanical force, greatly increasing the contact area between phosphogypsum and modified red mud, promoting their full mixing and reaction, and ensuring the stable removal of soluble phosphorus and the improvement of the activity of the raw materials. Without ball milling, the materials are not evenly dispersed and the reaction is not sufficient, which directly affects the subsequent hydration and gel formation, resulting in a decrease in the strength of the board.
[0069] In Comparative Example 8, the compounding ratio of the composite activator is adjusted to nano-SiO2:CaO:metakaolin = 1:4:5, and the performance of the gypsum board is lower than that of Example 1. A lower proportion of nano-SiO2 will result in insufficient active silicon to fully participate in gel formation. A higher proportion of metakaolin may disrupt the balance of alkaline environment and silicon-aluminum ratio, weakening the activation effect of slag. The original ratio of the three components is coordinated, which can achieve the synergistic effect of alkaline activation, active silicon supplementation and aluminum optimization, maximizing the activation of slag activity. Therefore, the performance decreases after adjusting the ratio.
[0070] The above only describes the preferred embodiments of the present application. It should be noted that those skilled in the art can make several improvements and refinements without departing from the principles of the present application, and these improvements and refinements should also be considered within the scope of protection of the present application.
Claims
1. A slag phosphogypsum synergistic activated gypsum board, characterized in that: The composition includes the following components in parts by weight: 50-60 parts of pretreated phosphogypsum, 25-35 parts of slag powder, 5-10 parts of composite activator, 1-3 parts of reinforcing fiber, 1-3 parts of self-repairing microcapsule, 0.1-0.5 parts of foaming agent and 20-40 parts of water.
2. The slag phosphogypsum synergistic activated gypsum board according to claim 1, characterized in that: The pretreated phosphogypsum is obtained by ball milling phosphogypsum and modified red mud in a mass ratio of 9:
1. The particle size D50 after ball milling is ≤15 μm, and the soluble phosphorus content is ≤0.1%. The slag powder is S95 grade blast furnace slag with a specific surface area of ≥500 m 2 / kg.
3. The slag phosphogypsum synergistic activated gypsum board according to claim 1, characterized in that: The composite activator is composed of nano-SiO2, CaO and metakaolin in a mass ratio of 3:4:3; the particle size of the nano-SiO2 is 20-50nm, and the purity of CaO is ≥95%.
4. The slag phosphogypsum synergistic activated gypsum board according to claim 1, characterized in that: The reinforcing fiber is silanized basalt fiber with a length of 3-6 mm and a diameter of 15-20 μm. The self-repairing microcapsule is a microsphere with a nano-silica sol core wrapped in a lignin shell and a particle size of 30-50 μm.
5. The slag phosphogypsum synergistic activated gypsum board according to claim 1, characterized in that: The foaming agent is prepared by mixing hydrogen peroxide and a protein foam stabilizer in a mass ratio of 1:1, and further comprises 0.3-0.8 parts of a setting agent, which is prepared by mixing citric acid and borax in a mass ratio of 3:
1.
6. A method for preparing the slag phosphogypsum synergistic activated gypsum board according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1. Preparation of pretreated phosphogypsum: Phosphogypsum and modified red mud were mixed in a mass ratio of 9:1, ball-milled to a D50 of ≤15 μm, then aged at 60°C for 24 h, centrifuged, and dried. S2. Preparation of self-healing microcapsules: Nanosilica sol and lignin solution were mixed in a volume ratio of 1:5 and spray-dried into microspheres. The shell was then cured by heat treatment at 150°C for 1 h. S3. Slurry preparation: dry mix pretreated phosphogypsum, slag powder, and composite activator; add water and stir, then add reinforcing fiber, self-repairing microcapsules, and foaming agent in sequence, stir evenly, and obtain slurry. S4. Step curing: After the slurry is injected into the mold, it is pre-cured at 60℃ / RH≥90% for 4 hours, then cured at 110℃ with normal pressure steam for 8 hours, and then carbonized with CO2 concentration of 20% for 24 hours.
7. The method for preparing slag phosphogypsum and activated gypsum board according to claim 6, characterized in that: In step S1, the ball mill uses zirconia ball milling beads, a ball-to-material ratio of 5:1, a rotation speed of 250 rpm, and a time of 2 h. In step S3, all components must be dried at 105°C to a moisture content of ≤0.5% before dry mixing. In step S4, the slurry heating rate is controlled to ≤5°C / h in the pre-curing stage, and the CO2 pressure in the carbonization treatment stage is 0.1 MPa.
8. The method for preparing slag phosphogypsum and activated gypsum board according to claim 6, characterized in that: The specific preparation method of the modified red mud is: The red mud raw material is placed in a ball mill, and zirconium oxide microballs are added at a ball-to-material ratio of 6:1 for ball milling. Deionized water is added and wet milled at 350 rpm for 1.5 hours to obtain a ball mill slurry, wherein the diameter of the zirconium oxide microballs is 3-5 mm and the solid content of the ball mill slurry is 40-45%. A sodium silicate solution with a mass% of 5% of the red mud is added to the ball mill slurry, and the mixture is transferred to a constant temperature stirred reactor and stirred at 200 rpm for 2 hours at 80-85° C. to obtain an activated slurry, wherein the modulus of the sodium silicate solution is 1.8 and the concentration is 40%. The activated slurry is poured into a centrifuge and separated at a centrifugal force of 4000 g for 10 minutes. The supernatant is discarded and the mixture is washed three times with deionized water until the conductivity of the filtrate is ≤100 μS / cm. The precipitate is dried in a blast drying oven at 105° C. to a moisture content of ≤2%, and pulverized to pass through a 200-mesh sieve to obtain a red mud intermediate. The red mud intermediate was placed in a muffle furnace, heated to 670±10°C at a rate of 5°C / min, and kept warm for 45 minutes. The red mud intermediate was then taken out and transferred to an air cooling device, where it was cooled with 5°C cooling air to below 80°C. The modified red mud was then placed in a dryer and cooled to room temperature to obtain modified red mud.
9. The method for preparing slag phosphogypsum and activated gypsum board according to claim 6, characterized in that: The specific preparation method of the self-healing microcapsules is as follows: preparing a 20% lignin aqueous solution, adjusting the pH to 10.5-11.0, mixing nano-silica sol and lignin solution in a volume ratio of 1:5, dispersing at a high speed of 1000 rpm for 30 minutes to form a homogeneous emulsion, spray drying using a spray drying process, and spray drying conditions are: inlet temperature 180±5°C, outlet temperature 80±5°C, atomization pressure 0.3MPa, and emulsion solid content controlled to 2%. Then, the collected microspheres are heat treated at 150°C for 1 hour to cause the lignin shell to undergo a glass transition to form a dense structure.
10. The method for preparing slag phosphogypsum and activated gypsum board according to claim 7, characterized in that: The specific method for preparing the pretreated phosphogypsum is: a) phosphogypsum and modified red mud were added to a ball mill in a mass ratio of 9:1, the ball mill using zirconia balls, a ball-to-material ratio of 5:1, and wet-milled at 250 rpm for 2 h to obtain a wet-milled slurry; b) Transfer the wet-milled slurry into an aging tank and age it at 60±2°C and a stirring rate of 50 rpm for 24±0.5 hours; c) centrifuging the aged wet-ground slurry at 3500 g for 5 min and discarding the supernatant; d) The precipitate is dried in a hot air circulation oven at 105°C to a moisture content of ≤0.5%, and then crushed to pass through a 325-mesh sieve to obtain pretreated phosphogypsum with a D50 of ≤15 μm.
Citation Information
Cited By
High-performance composite fireproof coating and preparation method thereof
CN121975356A
High-performance composite fireproof coating and preparation method thereof
CN121975356B
Matrix self-loading photocatalysis high-strength and high-toughness geopolymer and preparation method thereof
CN122254821A